PERANAN KUALITAS SPRITUAL ORANGTUA DALAM MENGEDUKASI PSIKOLOGIS KORBAN KEKERASAN PADA ANAK GEREJA BETHEL INDONESIA TAMAN LAGUNA INDAH - Tony Suhartono; Robertus Suryady; Suriana Suriana; Agustutina Sinaga; Yakobus Fernando Abton Wara (JURNAL BEATITUDES, 2023)
The quality of spirituality is when knowledge is the same as attitude and behavior. Broken personality is when knowledge is the same as attitude but not the same as behavior or knowledge is not the same as attitude, not the same as behavior. Caring for children is a heavy responsibility, because children will create a generation that will continue the dreams of their parents that have not been achieved. Good parents should maintain a harmonious relationship between family members. Harmonious relationships, full of attention, understanding and compassion will result in good behavior in children. Conversely, disharmony such as parental violence will affect the development of the child's soul that is not good, such as stubbornness, liars, and impolite. The child will depend on the first and foremost environment, namely his family, his father and mother who will determine him. Likewise regarding the diversity of children including in it, will be the responsibility of the parents. Parents have full responsibility for the growth and development of their children when they grow up to become knowledgeable and faithful people. The method used is lectures and discussion of the role of parents' spiritual qualities in educating the psychology of victims of child abuse. All stages have been carried out properly as evidenced by the great support the congregation has taken part in discussing this issue.